Barriers to transitioning to circular economy within firms in Western Balkans countries - Rexhepi Mahmutaj, Lura; Jusufi, Nora; Krasniqi, Besnik; Mazrekaj, Leonita; Krasniqi, Tringë (Frontiers in Sustainability, 2025)
IntroductionThe circular economy has gained considerable attention within academia and industry as a sustainable alternative to linear economic models that minimize waste and maximize resource value in the production cycle. Despite growing interest in adopting circular economy practices within firms, numerous challenges remain. We address this gap by investigating the barriers to transitioning to a circular economy, as the current implementation in practice often needs to be more complete.MethodsUsing a quantitative approach, this research examines the CE barriers influencing Western Balkans firms to become more environmentally responsible business. The analysis is based on data from the Regional Cooperation Council's Business Balkan Barometer 2024 database, compiled through the Business Opinion Survey, for which logistic regression analysis was employed.ResultsThe findings reveal that firms reporting barriers, such as added costs, lack of skills and experience, lack of consumer demand, and lack of government subsidies, are statistically significant in the probability of becoming more environmentally responsible business. By contrast, the lack of legal and regulatory framework was not found to be significant.DiscussionThe study contributes a comprehensive analysis of these barriers that validate and complement previous research, offering stakeholders within Western Balkan countries an additional perspective to overcome the current challenges, thereby fostering the transition to becoming a more environmentally responsible business.